Determining the intention to re-patronise shariah-compliant brand restaurants - Yuslina Liza binti Mohd Yusof (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
The growth of the global Muslim population has presented both opportunities and challenges to marketers in exploiting the growing Shariah-compliant market especially in the food service and hospitality industries. The demand for Halal food is growing worldwide due to increasing trade, tourism, and globalisation. In Malaysia, Muslim consumers want brands that convey genuine Islamic benefits and values because the brands will reflect them as Muslims. Misunderstanding on what the Shariah-compliant brand is especially in the food services industry can trigger a lot of doubts and anxieties. Therefore, the purpose of this study is to investigate the determinants of intention to re-patronise Shariah-compliant brand restaurants. The research framework consists of eight latent variables - seven exogenous and one endogenous. The exogenous variables consist of brand awareness, trust associated with Halal certification, brand of origin (BOO) association, perceived quality association (value for money, atmospheric, food taste and service personnel), attitude, subjective norms, and perceived behavioural control. Meanwhile, endogenous variable is the intention to re-patronise Shariah-compliant brand restaurants. This study also investigates the moderating effect of religiosity on consumers' intention to re-patronise Shariah-compliant brand restaurants. In addition, this study explains how the Customer-Based Brand Equity (CBBE) theory and the Theory of Planned Behaviour (TPB) framework were used in examining the determinants of intention to re-patronise Shariah-compliant brand restaurants. The data were collected via self-reporting questionnaires in the Klang Valley and the hypothetical relationships were examined using Structural Equation Modelling - Partial Least Square (SEM-PLS). A total of 531 respondents participated in this survey. The results from this study gave empirical support to the general structure incorporated in the research model. Brand awareness, perceived quality association, and attitude have significant and positive influence on intention to re-patronise Shariah-compliant brand restaurants. Meanwhile, trusts associated with Halal certification, subjective norms, perceived behavioural control, and brand of origin (BOO) were found to be not significant. In addition, the moderation effect between religiosity and attitude, subjective norms as well as perceived behavioural control cannot be established because the relationships were not significant. The findings from this study has advanced knowledge in Islamic marketing and branding which is currently very scarce by shedding evidence on the determinants of intention to re-patronise Shariah- compliant brand restaurants. Not only does this research contributes to the body of knowledge, these findings also provided input for managerial practices. The findings can assist organisations to create pragmatic actions which are useful and applicable in the food services industry, specifically in Shariah- compliant brand restaurants.